Continuous Cooling Transformation Diagrams of HSLA Steel for Seamless Tubes Production - Schindler, Ivo; Kawulok, Rostislav; Seillier, Yann; Kawulok, Petr; Opěla, Petr; Rusz, Stanislav; Vodárek, Vlastimil; Turoň, Rostislav (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
Three continuous cooling transformation diagrams were constructed for the HSLA steel containing Cr, Nb, V and N – standard CCT diagram as well as DCCT diagram including the effect of previous deformation for austenitization temperature of 1173 K, and another DCCT diagram for austenitization temperature of 1553 K. Combining the location of samples cut out of an continuously cast bloom with the material’s thermomechanical treatment, initial austenite grain size approx. 10 µm was obtained at low-temperature heating and more than 200 µm at high-temperature heating of the dilatometry samples. Previous deformation at temperature of 1173 K influenced decomposition of austenite not much, but the effect of coarse grain was enormous – by lowering the Ferrite-start temperature up to 473 K in comparison with the fine-grain structure. The initial coarse-grain microstructure accelerated the acicular ferrite formation. The developed diagrams can be used in a seamless tubes rolling mill for the stage of cooling from the finish-rolling temperature or for the subsequent heat treatment of tubes.